Discussion on Avoidance of Staining Problem in Cotton/CDPET Dyeing - Pervez, Md. Nahid; Inamdar, Umarsharif Y.; Talukder, Md. Eman; Rahman, Md. Ziaur; Khatun, Mst. Munera; Sultana, Mst. Zakia; Cai, Yingjie; Lin, Lina (MATEC web of conferences, 2017)
In this research, a novel approach has been proposed to remove stain problem from blended fabrics as an alternative option with traditional reduction clearing process. For this purpose, cationic dyeable polyester and cotton blended fabrics were dyed as traditional technique based on formulations approach and the colour strength (K/S), dye uptake (%) and the whiteness index properties were evaluated. The results of color strength indicated that dye was more uniformly absorbed by the blended fabric compared to the untreated fabric. In addition, when untreated fabric was dyed in the presence of a leveling agent (Lyogen DFTN), the K/S and levelness of dye uptake (%) values were enhanced. Finally, very less staining was observed that proved by CIE Whiteness Index values and indicates that formulation (F-IV) has more beneficial to reduce staining from Cotton/CDPET blended fabric (65/35).